Peer Group Member’s Demographic Effect on Promotional Choice for Sustainable Competitive Advantage - et al., Dr. Shashi Kala (International Journal of Advanced Science and Technology, 2019)
Intense competition in the field of marketing has forced marketing managers to formulate aggressive marketing strategies. In the past few years, marketing managers have been using coupons, rebates, shelf-price discounts and freebies as promotional tool to increase the effectiveness of their sales promotion efforts. Many studies have been conducted to investigate the influence of peer groups on consumer’s preference of brand and choice of product. Peer Group membership has been identified as a determinant of consumer behavior. Normally people align themselves to reference groups for forming their behavior and reference groups have been accepted by marketers as an important variable in determining consumer decision making. This paper discusses the effect of demographics of members of peer group, group cohesiveness and conformity on consumer behavior towards sales promotions. Two types of sales promotions have been discussed- hedonic and utilitarian.